Out of our minds : reason and madness in the exploration of Central Africa - Fabian, Johannes; Universität Frankfurt am Main. Frobenius-Institut. (Berkeley : University of California Press, 2000)
Travel, exploration, and occupation -- Living and dying -- Drives, emotions, and moods -- Things, sounds, and spectacles -- Communicating and commanding -- Charisma, cannabis, and crossing Africa: explorers in the land of friendship -- Making knowledge: the senses and cognition -- Making sense: knowledge and understanding -- Presence and representation.
Includes bibliographical references (p. 303-310) and index.
boek
Keywords: Ethnology -- Fieldwork -- Africa, Central; Ethnologists -- Africa, Central -- History; First contact of aboriginal peoples with Westerners -- Africa, Central -- History; Africa, Central -- Discovery and exploration -- German; Africa, Central -- Discovery and exploration -- Belgian; Africa, Central -- Description and travel